Structure and function of the archaeal exosome. (30th April 2014) - Evguenieva‐Hackenberg, Elena; Hou, Linlin; Glaeser, Stefanie; Klug, Gabriele
<x xml:space="preserve">Abstract</x> The RNA‐degrading exosome in archaea is structurally very similar to the nine‐subunit core of the essential eukaryotic exosome and to bacterial polynucleotide phosphorylase (PNPase). In contrast to the eukaryotic exosome, PNPase and the archaeal exosome exhibit metal ion‐dependent, phosphorolytic activities and synthesize heteropolymeric RNA tails in addition to the exoribonucleolytic RNA degradation in 3′ → 5′ direction. The archaeal nine‐subunit exosome consists of four orthologs of eukaryotic exosomal subunits: the RNase PH‐domain‐containing subunits Rrp41 and Rrp42 form a hexameric ring with three active sites, whereas the S1‐domain‐containing subunits Rrp4 and Csl4 form an RNA‐binding trimeric cap on the top of the ring. In vivo, this cap contains Rrp4 and Csl4 in variable amounts. Rrp4 confers poly(A) specificity to the exosome, whereas Csl4 is involved in the interaction with the archaea‐specific subunit of the complex, the homolog of the bacterial primase DnaG. The archaeal DnaG is a highly conserved protein and its gene is present in all sequenced archaeal genomes, although the exosome was lost in halophilic archaea and some methanogens. In exosome‐containing archaea, DnaG is tightly associated with the exosome. It functions as an additional RNA‐binding subunit with poly(A) specificity in the reconstituted exosome of Sulfolobus solfataricus and enhances the degradation of adenine‐rich transcripts in vitro. Not only the RNA‐binding cap but also the hexameric Rrp41–Rrp42 ring alone shows substrate selectivity and prefers purines over pyrimidines. This implies a coevolution of the exosome and its RNA substrates resulting in 3′‐ends with different affinities to the exosome. WIREs RNA 2014, 5:623–635. doi: 10.1002/wrna.1234 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.